Aboriginal and Torres Strait Islander health checks: sociodemographic characteristics and cardiovascular risk factors - Danielle C Butler; Jason Agostino; Ellie Paige; Rosemary J Korda; Kirsty A Douglas; Vicki Wade; Emily Banks (Public Health Research & Practice, 2022)
Objective: To quantify Aboriginal and Torres Strait Islander health check claims in Australian adults in relation to sociodemographic and health characteristics, including prior cardiovascular disease (CVD) and CVD risk factors.